2019
DOI: 10.1021/acsinfecdis.9b00424
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Inhibitor Taurolithocholic Acid Alters Colony Morphology, Specialized Metabolism, and Virulence of Pseudomonas aeruginosa

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 63 publications
1
28
0
Order By: Relevance
“…As metabolism often underlies phenotypic changes, we hypothesized that different ASM formulations induced different chemotypes of PAO1. P. aeruginosa has a well characterized specialized metabolome chemical signals produced by microorganisms to interact with their environment (46,47)), including six molecular families: homoserine lactones (HSLs), rhamnolipids (RHLs), alkyl quinolones (AQs), phenazines (PHZs), and the siderophores pyochelin (PCH) and pyoverdine (PVD) (48)(49)(50). These compounds are chemically and functionally diverse and include quorum sensors, small molecule virulence factors, and natural products.…”
Section: P Aeruginosa Produces Similar Specialized Metabolites In Almentioning
confidence: 99%
See 3 more Smart Citations
“…As metabolism often underlies phenotypic changes, we hypothesized that different ASM formulations induced different chemotypes of PAO1. P. aeruginosa has a well characterized specialized metabolome chemical signals produced by microorganisms to interact with their environment (46,47)), including six molecular families: homoserine lactones (HSLs), rhamnolipids (RHLs), alkyl quinolones (AQs), phenazines (PHZs), and the siderophores pyochelin (PCH) and pyoverdine (PVD) (48)(49)(50). These compounds are chemically and functionally diverse and include quorum sensors, small molecule virulence factors, and natural products.…”
Section: P Aeruginosa Produces Similar Specialized Metabolites In Almentioning
confidence: 99%
“…These compounds are chemically and functionally diverse and include quorum sensors, small molecule virulence factors, and natural products. P. aeruginosa specialized metabolites have been detected in CF sputum (32)(33)(34) and associated with pathogenicity and virulence (24,50,51).…”
Section: P Aeruginosa Produces Similar Specialized Metabolites In Almentioning
confidence: 99%
See 2 more Smart Citations
“…This approach has been applied to decipher microbe-microbe chemical communication and changes in metabolite production between microbial colonies grown in different environmental conditions. (6,26,27) IMS is especially valuable for the comparison of metabolites of defined strains because changes in production, as measured by ion intensity, can be specifically and rapidly detected and evaluated in the context of genetic differences. (28) IMS analysis of WT V. fischeri compared to Biofilm-Up and Biofilm-Down strains revealed that several metabolites were significantly upregulated in Biofilm-Up compared to the other strains.…”
Section: Introductionmentioning
confidence: 99%